Asymmetries in the effects of drivers of brand loyalty between early and late adopters and across technology generations - Lam, Shun Yin (2015)
Mobile marketing activities are growing at a rapid pace. The success of mobile marketing hinges on consumers' adoption of mobile devices. However, consumers' mobile device adoption is not well understood at the brand (e.g., Apple, Nokia, Samsung) level. We propose a conceptual framework linking mobile device brand loyalty (repurchase intention) to its drivers including perceived value, brand satisfaction, brand attachment and trust, and develop hypotheses about the moderating roles of adopter type and mobile technology generation in some of these linkages. We test these hypotheses using structural equation modeling on a unique cross-sectional dataset of attitudes toward mobile phone brands spanning two technology generations, 2.5G and 3G. The results reveal important asymmetries between adopter types and between technology generations: early adopters of mobile devices emphasize perceived value, whereas late adopters rely on brand satisfaction in developing brand loyalty; and consumers depend more on trust and less on perceived value in developing loyalty for the new generation than for the existing generation. We outline how brand managers of mobile devices should adapt their marketing strategies to different adopter types and technology generations.